A mini review on thermoplastic composite inner blades for vertical-axis wind turbines (VAWT): Aerodynamic and mechanical insights - Nasirinia, Younes; Azizi, Seied Hossein; Pourdizaji, Mohammadreza (Journal of Composites and Compounds, 2024)
As global demand for more sustainable energy grows, wind energy has emerged as a key renewable energy source, especially when it pertains to the aerodynamic optimization of wind turbine blades for aerodynamic efficiency. When it comes to wind turbine blades, thermoplastic composites are gaining significant interest. This paper analyzes the impact thermoplastic composite inner blades will have on vertical axis wind turbine (VAWT) performance. Thermoplastic composite inner blades may enhance performance due to low weight and design flexibility to achieve improved start-up and increased aerodynamic efficiency along with toughness and cyclic load fatigue resistance for increased structural reliability of the blades. Advanced technologies for the manufacturing of thermoplastic composite blades will enable the use of precision manufacturing and easy or rapid repairs. Subsequently, an evaluation of the effectiveness of the various strategies are considered, including a thorough analysis of various performance enhancing strategies and successes on VAWT performance, and concludes with various effective strategies. Therefore, as an evaluation of issues and resolved issues related to VAWTs, the findings will assist future research efforts focusing on addressing aerodynamics and mechanically optimizing VAWTs more effectively.